Multivariate statistical process control in annual pharmaceutical product review. (September 2018) - Tôrres, Adamastor R.; de Oliveira, Antônio Diógenes P.; Grangeiro, Severino; Fragoso, Wallace D.
Highlights: A five years real monitoring in a pharmaceutical industry are presented. Multivariate Control Process was used for Annual Pharmaceutical Product Review. Reconstruction-based Contributions was used for fault direction detection. Abstract: Annual Product Review recommending by the Food and Drug Administration and the International Conference on Harmonization is a periodic assessment of products quality to verifying the consistency of the production process and the quality of the finished product. In this work it was performed an annual product review using multivariate statistical process control. Multivariate control charts was used for the periodic evaluation of the Hydrochlorothiazide 25 mg tablet, produced between 2009 and 2013 in the Pharmaceutical Laboratory of Pernambuco (Brazil). The procedure has allowed one to monitor and diagnose deviations in the production process. A corrective action was taken in the process by the Quality System in 2011 and the methodology applied was used to evaluate this action's effectiveness. Through the Multivariate Statistical Process Control it was possible to make an annual product review in accordance with the pharmaceutical industry regulatory requirements.